Optimal Inflation Weights in the Euro Area - Daniela Bragoli; Massimiliano Rigon; Francesco Zanetti (Birkbeck, University of London, Birkbeck Centre for Applied Macroeconomics (BCAM), 2015)
This study investigates the appropriate measure for stabilizing inflation in the Euro Area. We use a model that accounts for both the heterogeneity observed in the degree of price rigidities across regions and sectors, and asymmetry of real disturbances in relative prices. Our work shows that the optimal weights to assign to each region or sector result from complex interactions between the degree of price stickiness, economic size and the distribution of shocks within regions.
Keywords: E52; F41; 330; Optimal monetary policy; Euro Area regions; asymmetric shocks; asymmetric price stickiness